SISTEM PENCARIAN DATA PENDUDUK YANG TIDAK EFISIEN DI KELURAHAN PATANE III KECAMATAN PORSEA: REKOMENDASI UNTUK PENINGKATAN - Simamora, Lambok Lamtulus; zebua, Indrawan foera-era; pasaribu, Sonia; Siahaan, Mahesa Pratama; sitompul, Perjuangan; Saragih, Tiurma Elita (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2025)
Patane III Subdistrict, Porsea District, faces challenges in an inefficient population data search system. This problem causes delays in administrative services, lack of data accuracy, and increases the workload for sub-district officers. This community service aims to analyze the causes of inefficiency in the population data search system and provide recommendations for information technology-based solutions. The carry out activities sed was direct observation and interviews with related parties. The research results show that the main causes are the use of a manual recording system, lack of data integration, and limited human resources trained in digital data management. As a recommendation, it is recommended to implement a digital-based information system, training for officers, and integration with the national population system to increase efficiency and accuracy of data.